Distinct work‐related, clinical and psychological factors predict return to work following treatment in four different cancer types. Issue 3 (21st March 2012) - Cooper, Alethea F.; Hankins, Matthew; Rixon, Lorna; Eaton, Emma; Grunfeld, Elizabeth A.
Abstract: Objective: Many factors influence return to work (RTW) following cancer treatment. However specific factors affecting RTW across different cancer types are unclear. This study examined the role of clinical, sociodemographic, work and psychological factors in RTW following treatment for breast, gynaecological, head and neck, and urological cancer. Methods: A 12‐month prospective questionnaire study was conducted with 290 patients. Cox regression analyses were conducted to calculate hazard ratios (HR) for time to RTW. Results: Between 89–94% of cancer survivors returned to work. Breast cancer survivors took the longest to return (median 30 weeks), and urology cancer survivors returned the soonest (median 5 weeks). Earlier return among breast cancer survivors was predicted by a greater sense of control over their cancer at work (HR 1.2; 95% CI: 1.09–1.37) and by full‐time work (HR 2.1; CI: 1.24–3.4). Predictive of a longer return among gynaecological cancer survivors was a belief that cancer treatment may impair ability to work (HR 0.75; CI: 0.62–0.91). Among urological cancer survivors constipation was predictive of longer RTW (HR 0.99; CI: 0.97–1.00), whereas undertaking flexible working was predictive of returning sooner (HR 1.70; CI: 1.07–2.7). Head and neck cancer survivors who perceived greater negative consequences of their cancer took longer to return (HR 0.27; CI: 0.11–0.68). Those reporting better physical functioning returned sooner (HR1.04; CI: 1.01–1.08). Conclusion: A different profile of predictive factors emerged for the four cancer types. In addition to optimal symptom management and workplace adaptations, the findings suggest that eliciting and challenging specific cancer and treatment‐related perceptions may facilitate RTW. Copyright © 2012 John Wiley & Sons, Ltd.